Public Activities of Youth: Participation Motives - Сергей Леонидович Лунин; Анастасия Андреевна Левшина (Rossijskij psihologičeskij žurnal., 2015)
The article deals with the motivational component of the sense-value sphere of young people participating in public activities. The authors oTer an overview of domestic and foreign sources on this problem, as well as results of a survey of young people of Rostov-on-Don. Sociological, psychological, and political studies undertaken in the UK, France, Belgium and Canada are among foreign sources discussed in this article. Foreign authors distinguish two predominating motives: a desire to help others and make new friends. The review of Russian sources concerning the problem starts from the studies of the 90-ies of the XX century – the period of formation of youth public activities in the form in which it exists today. The authors also consider modern works describing motivational component of young people’s participation in various social initiatives. The article notes that the Russian research in this area is characterized by a focus on various political organizations and informal youth organization, while public activities in the Ueld of social service (volunteer organizations) remain out of sight. The authors oTer the results of their own survey of young people of Rostov-on-Don. The survey has been devoted to the motivation to participate in social activities. Members of various youth organizations, as well as students, who were not interested in volunteer initiatives, have taken part in it. According to the survey Undings, diTerent motives, which conventionally are grouped into three groups – social, personal, and socially neutral – predominate in diTerent groups of young people (representatives of various public organizations; students who are not involved in this form of activity).